Bone marrow aspirate combined with low-level laser therapy: A new therapeutic approach to enhance bone healing - Nagata, Maria J.H. [UNESP]; Santinoni, Carolina S. [UNESP]; Pola, Natália M. [UNESP]; De Campos, Natália [UNESP]; Messora, Michel R.; Bomfim, Suely R.M. [UNESP]; Ervolino, Edilson [UNESP]; Fucini, Stephen E.; Faleiros, Paula L. [UNESP]; Garcia, Valdir Gouveia [UNESP]; Bosco, Álvaro Francisco [UNESP] (Elsevier, 2013)
This study evaluated the influence of bone marrow aspirate (BMA), low-level laser therapy (LLLT) and their combination on bone healing in surgically created critical-size defects (CSDs) in rat calvaria. 40 rats were divided into four groups: C (control), BMA, LLLT and BMA/LLLT. A 5 mm diameter CSD was created in the calvarium of each animal. In Group C, the defect was filled by blood clot only. In Group BMA, the defect was filled with BMA. In groups LLLT and BMA/LLLT, the defect received laser irradiation (InGaAlP laser), was filled with blood clot or BMA respectively, and irradiated again. Animals were euthanized 30 days postoperatively. Histomorphometric and immunohistochemical analyses were performed. Newly formed bone area (NFBA) was calculated as percentage of the total area of the original defect. Proliferating cell nuclear antigen (PCNA), runt-related transcription factor 2 (Runx2) and osteocalcin (OCN) immunohistochemical staining were performed. PCNA-positive, Runx2-positive and OCN-positive cells were quantified. Data were statistically analyzed. Group BMA/LLLT had significantly greater NFBA than groups C, BMA or LLLT. Group BMA presented significantly greater NFBA than control, while group LLLT did not. Group BMA/LLLT presented a significantly higher number of PCNA-positive and OCN-positive cells than any of the other groups. Groups BMA/LLLT and BMA showed a significantly lower number of Runx2-positive cells than groups C or LLLT. The combination of BMA/LLLT yielded significantly greater bone formation in surgically created CSD in rat calvaria when compared to control, or either treatment alone. © 2013 Elsevier B.V. All rights reserved.
Keywords: Animal model; Bone marrow; Bone regeneration; Immunohistochemistry; Low-level laser therapy; Rats; cycline; osteocalcin; transcription factor RUNX2; animal experiment; animal model; animal tissue; blood clot; bone marrow biopsy; calvaria; controlled study; fracture healing; immunohistochemistry; laser; low level laser therapy; male; morphometrics; nonhuman; ossification; postoperative period; priority journal; rat; Animalia; Rattus